2010
DOI: 10.1002/ceat.200900566
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Dimensional Mass‐Transfer Model of a Flat‐Plate Dialyzer with Ultrafiltration Operation

Abstract: A two-dimensional theoretical model of a flat-plate dialyzer with ultrafiltration operation was developed in this study. The two-dimensional velocity profile of the fluid and the concentration distribution in the membrane of the dialysis system with ultrafiltration operation were also derived. The Crank-Nicolson method was used to numerically solve the two-dimensional theoretical model. The influences of the retentate phase flow rate, dialysate phase flow rate, ultrafiltration flow rate and channel thickness r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…The experimental work is cost prohibitive at the present time and there is only the available experimental data from the flat-plate dialyzer for confirmation. The present study could be analogized from those in our previous work on the flat-plate module [ 35 ]; this is a forthcoming work for our laboratory and will be conducted in the near future. In order to validate the theoretical predictions of the two-dimensional mathematical formulations in the concentric circular membrane dialyzer, a comparison was made with the experimental results conducted by the flat-plate dialyzer under ultrafiltration operation in our previous work [ 35 ] which neglected the tube curvature effect in the concentric tube [ 36 ].…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…The experimental work is cost prohibitive at the present time and there is only the available experimental data from the flat-plate dialyzer for confirmation. The present study could be analogized from those in our previous work on the flat-plate module [ 35 ]; this is a forthcoming work for our laboratory and will be conducted in the near future. In order to validate the theoretical predictions of the two-dimensional mathematical formulations in the concentric circular membrane dialyzer, a comparison was made with the experimental results conducted by the flat-plate dialyzer under ultrafiltration operation in our previous work [ 35 ] which neglected the tube curvature effect in the concentric tube [ 36 ].…”
Section: Resultsmentioning
confidence: 79%
“…A two-dimensional mathematical model of the concentric tubular dialysis-and-ultrafiltration module is developed theoretically. Though the mass-transfer characteristics in the present study could be analogized from those in our previous work on the flat-plate module [ 35 ], the manners of velocity and transport across the membrane are somehow different and the mass-transfer mathematical formulation is relatively complicated. This study actually extends the one-dimensional modeling of the flat-plate module to a two-dimensional analysis of the concentric tubular dialysis-and-ultrafiltration system in the present study to obtain improvements in dialysis efficiency and rate; however, no theoretical study in its simplified expression has been reported in the literature for a concentric tubular dialyzer with an ultrafiltration operation.…”
Section: Introductionmentioning
confidence: 96%
“…However, for the hollow fiber system with ultrafiltration, the velocity distribution is more complex and is developed by a two-dimensional mathematical model to simulate the mass transport in a hollow-fiber artificial kidney, assuming the shell side as a porous medium [ 10 ]. The influence of ultrafiltration operations on mass transfer in a hollow-fiber hemodialyzer was discussed by Jagannathan and Shettigar [ 11 , 12 ] and applied in the context of a circular conduit dialyzer [ 13 ] and parallel-plate dialyzer with ultrafiltration operations [ 14 ]. The treatment time tolerated by patients can be reduced by applying a hemodialysis membrane with ultrafiltration operations in hollow-fiber hemodialyzers [ 15 , 16 ], which is the active cure to elongate the lives of people suffering from end-stage renal diseases (ESRD) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The aims in this work are to develop the two-dimensional mathematical statements of a hollow-fiber membrane dialyzer with operating ultrafiltration and to obtain the theoretical predictions compared with experimental data. The general applicability of such a mathematical formulation was developed similar to the parallel-plate dialysis-and-ultrafiltration system in our previous work [ 14 ]. The previous work was confined to a parallel-plate channel while the present paper deals with the conjugated problems in a circular tube with an imaginary shell.…”
Section: Introductionmentioning
confidence: 99%
“…Tu et al [13] developed a theoretical model for a twodimensional flow of filtrate in a flat-plate dialyzer with the operation of ultra filtration In their study, they used the Crank-Nicolson technique to numerically solve the governing theoretical model. They also derived the fluid velocity profile and the concentration distribution in the dialysis system's membrane with the ultra filtration operation.…”
Section: Introductionmentioning
confidence: 99%